Joint inversion of porosity for establishing velocity-conductivity relationship by using Levenberg-Marquardt and singular value decomposition - Khairy , Hilfan (2007)

(untitled)
The velocity information is very crucial in seismic processing particularly to generate seismogram synthetic and fluid type analysis. Pseudo velocity log can be constructed by using conductivity log (reverse of resistivity). The relationship of velocity and conductivity in this paper is developed by joint porosity optimization using integrated Levenberg-Marquardt and SVI) techniques. The main goal of the research is to construct an alternatively new technique velocity-conductivity relationship based on inversion process. The sonic-porosity and electrical-porosity are formulated and theu iteratively optimized to yield the most fitting parameter. The perturbation model resulted is then compared to the log properties (real data). Froni synthetic data resulted R=0.9019 and R=0.3286 of near and far input model parameter respectively. If the most sensitive model perturbation is eliminated, it yields R=0.9475. Â©2007 IEEE.